Haematology of pregnant West African dwarf ewes fed siam weed-based rations (2004)
There is relatively scanty information on normal blood values for sheep in Nigeria as regards the nature and the level of forage inclusion in the diets. The study was set up to assess the effects of siam weed on blood chemistry of pregnant West African Dwarf (WAD) sheep. Sixteen WAD sheep that have lambed once were allocated in a completely randomized design to four diets with different levels of siam weed leaf meal (SWLM) diets inclusion: 0% (Diet A), 15% (Diet B), 30% (Diet C) and 45% (Diet D). Variations in haematological parameters due to treatments were inconsistently significant except for Erythrocyte/ red blood cell (RBC). The Leukocyte/white blood cell (mm3 xlO3) varied from 5.64 (diet B) to 8.81 (diet A) in the last trimester. The lowest packed cell volume (28%) was obtained for sheep on 30% siam weed leaf meal (SWLM). Erythrocyte values were low ranging between 5.71 and 6.37. White blood cell was normal and ranged from 5.64 in 15% to 8.81 in 0% SWLM. The values for packed cell volume slightly increased in animals on diets 0% and 45% SWLM at the end of pregnancy while those of 15% and 30% remained normal. Mean corpuscular volume (ranged 47.50 - 53.25) was beyond the normal range at late pregnancy. The results showed that pregnant sheep could tolerate the siam weed leaf meal at levels between 15 and 45% dietary inclusion without a significant alteration of the blood constituents.